2019
DOI: 10.1139/apnm-2018-0734
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-lowering exercise effect is greater in hyperhomocysteinemic people living with HIV: a randomized clinical trial

Abstract: Elevated concentration of homocysteine has been identified as an independent risk factor for the development of cardiovascular disease and is frequently associated with oxidative stress. Moreover, studies have shown that people living with human immunodeficiency virus (PLHIV) present elevated concentration of homocysteine and oxidative stress compared with people without HIV. Our purpose was to describe blood homocysteine and oxidative stress markers in PLHIV and those without HIV infection, and to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…The screening cohort had a P-homocysteine mean of 13.0 μmol/l, consistent with 13.1 and 15.1 μmol/l in previous studies of PLHIV on ART. 40,41 By way of confirmation of our findings, a study by Remacha et al 42 also showed that treatment with vitamin B 12 and folic acid decreased the levels of P-homocysteine and increased the levels of B 12 and folate in a cohort of PLHIV. This is a pattern well known from studies of HIV-negative elderly people with or without cognitive impairment receiving vitamin B supplementation.…”
Section: Discussionsupporting
confidence: 80%
“…The screening cohort had a P-homocysteine mean of 13.0 μmol/l, consistent with 13.1 and 15.1 μmol/l in previous studies of PLHIV on ART. 40,41 By way of confirmation of our findings, a study by Remacha et al 42 also showed that treatment with vitamin B 12 and folic acid decreased the levels of P-homocysteine and increased the levels of B 12 and folate in a cohort of PLHIV. This is a pattern well known from studies of HIV-negative elderly people with or without cognitive impairment receiving vitamin B supplementation.…”
Section: Discussionsupporting
confidence: 80%
“…Similar effects are seen in PWH, where exercise attenuates markers of inflammation, including high-sensitivity C-reactive protein, TNF-α, IL-6, and IL-1β (32–34). We, and others, have demonstrated that combined exercise attenuates ART-induced redox imbalance and alleviates oxidative damage in PWH (35,36). Exercise training promotes mitochondrial biogenesis and enhances mitochondrial dynamics (37) and can partially restore mitochondrial metabolism impaired by ART.…”
Section: Exercise Interventions To Counteract Sarcopenia In Pwhmentioning
confidence: 81%
“…Acute exercise creates an inflammatory environment responsible for recovery and adaptation from an exercise session in healthy individuals 16 , but it is not known whether the magnitude of this damage is more exacerbated in HIV-infected individuals. Furthermore, there are few studies in the literature that aim to investigate the effects of resistance training on oxidative stress 17,18 and inflammatory markers in PLH 19 . Therefore, this study aims to investigate the effect of a single resistance exercise (RE) session on inflammatory markers and oxidative stress in women living with HIV.…”
Section: Introductionmentioning
confidence: 99%